Valuation of Closely-Held Firms: Another Look - William P. Dukes; Oswald D. Bowlin (Journal of Small Business Finance, 1993)
For the most part, closely-held firms must be valued using proxies for market data which are not available. Valuation approaches described in the literature are used by practitioners with exceptions demanded by circumstances. Results of the survey confirm statements of others that substantial discounts for non-marketability and minority interest are usually appropriate.
Keywords: G32; 650; Valuation; Closely-Held; Small Business